Emotional avoidance and social support interact to predict depression symptom severity one year after traumatic exposure. (February 2020) - Forbes, Courtney N.; Tull, Matthew T.; Xie, Hong; Christ, Nicole M.; Brickman, Kristopher; Mattin, Mike; Wang, Xin
Highlights: Emotional avoidance predicts depression severity 12-months after traumatic exposure. High emotional avoidance with low social support predicts most severe depression. Low social support is a risk factor for depression following traumatic exposure. Abstract: Individuals exposed to a traumatic event commonly develop symptoms of depression, a psychiatric disorder associated with a number of negative clinical and public health consequences. Both intrapersonal and interpersonal risk factors have been associated with heightened risk for depression following traumatic event exposure; however, less is known about how these risk factors may interact to predict trauma-exposed individuals' risk of subsequently developing depression symptoms. This study examined the interactive influence of emotional avoidance (an intrapersonal risk factor) and perceived social support (an interpersonal risk factor) on the development of depression symptoms over a one-year period among N = 46 individuals recruited shortly after visiting a hospital emergency department for treatment following exposure to a traumatic event. Results revealed a significant main effect of emotional avoidance on 12-month depression symptoms. The main effect was qualified by an emotional avoidance by perceived social support interaction: the relation of emotional avoidance to 12-month depression symptoms was positive and significant only for individuals with low levels of perceived social support. Results highlight the need to consider both intrapersonal and interpersonal risk factors, as well as their interaction, when predicting which individuals may be most at risk to develop depression following traumatic event exposure.